Implementation of Artificial Intelligence-Based Deep Learning Approach in Learning to Present Negotiation Texts in Front of the Class - Zilvia Agnes; Amril Amir; Farel Olva Zuve; Ayu Gustia Ninggsih (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The deep learning approach is a meaningful learning approach, mindful learning approach, and joyful learning approach that is believed to be able to improve the learning process and outcomes. The deep learning approach in this study is integrated with artificial intelligence. The objectives of this study are to describe: 1) the learning plan for presenting negotiation texts in front of the class using an artificial intelligence (AI)-based deep learning approach; 2) the learning outcomes of presenting negotiation texts in front of the class using an AI-based deep learning approach. This type of research is qualitative research with a descriptive method. This study took place in the 2025/2025 academic year at SMA Negeri 16 Padang. The research subjects consisted of a grade X Indonesian language teacher and 30 grade X students of SMA Negeri 16 Padang who were divided into six study groups. Data were collected through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. Data validity was obtained through triangulation techniques of sources and methods. The results of the study indicate that the learning plan for presenting negotiation texts has been prepared in accordance with the principles of AI-based deep learning, which includes student-centered learning activities and encourages active involvement in the learning process. Furthermore, learning outcomes demonstrated an improvement in students' ability to present negotiation texts with greater confidence, systematicity, and communication. However, several challenges remained, such as time constraints, teacher preparedness, and varying student motivations. Overall, the implementation of AI-based deep learning had a positive impact on students' ability to present negotiation texts.